Effect of particle morphology, compaction, and confinement on the high strain rate behavior of sand - De Cola, F; Pellegrino, A; Glößner, C; Penumadu, D; Petrinic, N (Springer, 2017)
The effect of grain shape, size distribution, intergranular friction, confinement, and initial compaction state on the high strain rate compressive mechanical response of sand is quantified using Long Split Hopkinson Pressure Bar (LSHPB) experiments, generating up to 1.1 ms long load pulses. This allowed the dynamic characterisation of different types of sand until full compaction (lowest initial void ratio) at different strain rates. The effect of the grain morphology and size on the dynamic compressive mechanical response of sand is assessed by conducting experiments on three types of sand: Ottawa Sand with quasi-spherical grains, Euroquartz Siligran with subangular grains and Q-Rok with polyhedral grain shape are considered in this study. The adoption of rigid (Ti64) and deformable (Latex) sand containers allowed for quasi-uniaxial strain and quasi-uniaxial stress conditions to be achieved respectively. Additionally, the effect of intergranular friction was studied, for the first time in literature, by employing polymer coated Euroquartz sand. Appropriate procedures for the preparation of samples at different representative initial consolidation states are utilized to achieve realistic range of naturally occurring formations of granular assembly from loose to dense state. The results identify material and confining sample state parameters which have significant effect on the mechanical response of sand at high strain rates and their interdependency for fut ure integration into rate dependent constitutive models.